Development of a High-Performance Trichoderma Mutant for Enhanced Cellulase Production Through UV-Induced Random Mutagenesis - Seungjun Kim; Iksu Ha; Yun-Yeong Lee; Junseo Lee; Jeonghee Yun (Journal of Fungi, 2025)
Ultraviolet (UV)-induced mutagenesis is a cost-effective and straightforward technique for introducing random genetic variations without the use of chemical reagents or genetic engineering. It is commonly employed to enhance enzyme activity in industrial trains. In this study, Trichoderma sp. was exposed to UV radiation at varying distances (4, 9, and 13 cm) and durations (2, 4, 6, and 8 min) to induce mutations. The activities of endoglucanase (EG), β-glucosidase (BGL), and cellobiohydrolase (CBH) were assessed following treatment. The 4 cm exposure distance yielded the highest enhancement, with EG, BGL, and CBH activities increasing 1.5-, 1.3-, and 0.9-fold, respectively. When the distance was fixed at 4 cm, the optimal exposure time was identified as 4 min, yielding further enhancements of 1.9-, 1.6-, and 1.4-fold, respectively. The resulting mutant, designated Mut-4, was scaled up in a 10-L bioreactor to assess its industrial applicability. Mut-4 retained its enhanced performance, achieving 1.9-, 2.0-, and 1.4-fold enhancements in EG, BGL, and CBH activities, respectively, compared with the original strain. These findings indicate that combining UV-induced mutagenesis with basic screening is an effective strategy for enhancing cellulolytic enzyme production, representing a promising approach for lignocellulosic biomass conversion.